Teaching stage in question : formation and implications - Conte, Elaine; Gutierre, Liliane dos Santos (Universidade Estadual de Campinas, 2021)
Teaching work and the educational practice itself in higher education then brings dualities between formation and performance, inverted positions, opposite positions or simplifying divisions between the one who teaches (supervisor) and the other who learns (intern). The study, based on experiences of teacher education, discusses the issue of internship in higher education as a condition of possibility to think about education in a shared way, whose guiding principles involve a sensitivity towards each other, by scientific-professional evidence. related to the field of academic management and higher education. The research aimed to monitor the scientific advances approached by the academy, through experiences recorded in documented reports, in order to shed light on the theme of the teaching internship for contemporary education and the reality of the current challenges of higher education engagement. In fact, such concern requires a formative twist to overcome Manichean positions, promote the exchange of studies and pedagogical practices, developing the student's reflective thinking with the teacher in a variety of interdisciplinary situations, revealed in the circularity of planning, evaluating and understanding own joint constitution of the didactic organization, which involves the appreciation of cooperative and democratic experiences as a mark of the solidary presence of the teaching act.